2017
DOI: 10.1136/bmjopen-2016-014986
|View full text |Cite
|
Sign up to set email alerts
|

Predicting late-onset sepsis by routine neonatal screening for colonisation by gram-negative bacteria in neonates at intensive care units: a protocol for a systematic review

Abstract: IntroductionHospitals conduct extensive screening procedures to assess colonisation of the body surface of neonates by gram-negative bacteria to avoid complications like late-onset sepsis. However, the benefits of these procedures are controversially discussed. Until now, no systematic review has investigated the value of routine screening for colonisation by gram-negative bacteria in neonates for late-onset sepsis prediction.Methods and analysisWe will conduct a systematic review, considering studies of any d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Septicaemia is a major complication in the preterm neonate 2 . We showed a significant association between the presence of ETT bacterial colonisation and rates of septicaemia.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…Septicaemia is a major complication in the preterm neonate 2 . We showed a significant association between the presence of ETT bacterial colonisation and rates of septicaemia.…”
Section: Discussionmentioning
confidence: 51%
“…22 Septicaemia is a major complication in the preterm neonate. 2 We showed a significant association between the presence of ETT bacterial colonisation and rates of septicaemia. Harris et al also reported that septicaemia was significantly more likely in neonates with colonised tracheas.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Pediatric sepsis accounts for approximately 8% of all critically ill children 27 . In 2020 WHO called for global action on sepsis with a focus on improving data from low-income countries with better definitions for sepsis and more information on microbiological aspects and antibiotic resistance 28,29 .…”
Section: Discussionmentioning
confidence: 99%
“…During our study, we had two separate periods where screening was useful in identifying spread of colonisation without the development of bloodstream infection with resistant Enterobacter between patients leading to enhanced infection control practices and changes to equipment cleaning regimens. Future studies should assess more effective strategies for targeted surveillance for GNB in the neonatal population 4. It is important to recognise that screening has other important roles in understanding and managing the emergence of resistant-strain colonisation or to appropriately modify local antibiotic protocols for LOS.…”
mentioning
confidence: 99%